(untitled) (Journal of Business Management and Accounting, 2022)
As the world moves towards a technological era, various innovations have been introduced across different industries in order to meet customers’ expectations and enhance service quality. Self-service Technology (SST) is one innovation that can be commonly found across industries, and has gained high popularity among users. The main objective of this study is to examine the factors that affect customer intention in using SST, specifically among Generation Z. It examines the relationship between the independent variables of perceived ease of use, perceived usefulness, need of interaction, and technology anxiety and the dependent variable of customer intention in using SST. A questionnaire survey adopted in this study secured the required information from 152 target respondents. Analyses of responses explained 65.5% variances in customer intention of using SST. The research findings established through data analysed with SPSS version 27 application, suggest that perceived ease of use and perceived usefulness have positive significant relationships towards customer intention of using SST, but no significant relationship was found on need of interaction and technology anxiety in customer intention of using SST. Therefore, in order to encourage and attract potential and future users to utilise the service of SST, the system and function of SST need to be upgraded consistently to ensure it brings benefits and usefulness to users. Besides, a company can also educate users on ways to operate the SST in order to enhance the level of ease of use, and to increase the awareness of the usefulness of SST among users. The limitations and recommendations of future study are discussed at the end of the paper.